Risco de câncer utilizado como estratégia de governamentalidade no Programa de Políticas e Ações para Prevenção do Câncer no Brasil - Lima, Adriana Pessoa (2011)
The actions taken by the government in the management of cancer in the world has constituted this disease as a risk by placing all the people on the border between health and disease in order to promote the filiation to certain modes of existence of being healthy. But official discourses aiming populations haven’t always made use of the actual discursive strategy which articulates different social actors in search of health by means of risk device. In this work, we try to understand the conditions that made it possible for the risk discourse to become a global strategy to fight the disease and be inscribed in the practices of biopolitics in contemporary West. Based on the Foucaultian, theoretical and methodological frames, this research aims to analyze the constitution of the discourse of cancer as a risk in order to discuss the historical and cultural and discursive construction and its different uses and effects when organizing, regulating and governing social life. We also aim to understand the relationship between the policy of cancer prevention in Brazil and global health policies, to the extent that the contemporary management of health is linked to a sanitary transnational project that builds a government agenda to be adopted throughout nations. Finally, to contextualize the discourses that promote and sustain cancer as a risk for everyone, we sought to analyzed the Brazilian version of the document released by the WCRF / AICR in 2009 entitled "Policies and Actions for the Prevention of Cancer in Brazil: food, nutrition and physical activity" in order to understand the power procedures that enable the control the lifestyles of the population in terms of strategies and tactics. This study highlights the development of a health agenda that aligns political interests and individual aspirations in terms of health and longevity, so that the discourse of cancer instituted works for the exercise of political power. It is therefore a technology of attention / care for life, with the effect of promoting a hygienic society.